Analysis of Input and Output Ripples of PWM AC Choppers - Dahono, Pekik Argo; Amirudin, Dessy; Rizqiawan, Arwindra; Deni, Deni (Journal of Engineering and Technological Sciences, 2008)
This paper presents an analysis  of input and output ripples of PWM AC  choppers.  Expressions  of  input  and  output  current  and  voltage  ripples  of single-phase PWM AC choppers are first derived. The derived expressions are then  extended  to  three-phase  PWM  AC  choppers.  As  input  current and  output voltage ripples specification alone cannot be used to determine the unique values of inductance and capacitance of the LC filters, an additional criterion based on the  minimum reactive  power  is  proposed.  Experimental results  are included  in this paper to show the validity of the proposed analysis method.